Reasons Why Not: A Critical Review of the Television Series 13 Reasons Why - Cruikshank, Emily C.; Sevigny, Phillip R. (Canadian Journal of Counselling and Psychotherapy, 2020)
Since its initial release as a Netflix television series in 2017, 13 Reasons Why has caught the attention of professionals and viewers alike because of its gripping storylines and controversial content. The show’s explicit nature has prompted mental health professionals to draw the public’s attention to the possibility of suicide contagion, especially among adolescent viewers. This paper is a comprehensive review of the show, a review of the current research on its epidemiological impact on the public, and a guide for mental health professionals and the general public on how to respond to the current information that we know about the show and its possible effects on viewers.